Insights into early cochlear damage induced by potassium channel deficiency - Rias, Ezequiel Ignacio (2025)
Hearing loss (HL) is the most common sensory disorder, caused by genetic mutations and acquired factors like presbycusis and noise exposure. A critical factor in HL development is the dysfunction of potassium (K+) channels, essential for sensory cell function in the organ of Corti (OC). Inner and outer hair cells (IHCs and OHCs) convert sound into electrical signals, while supporting cells (SCs) maintain ionic and structural balance. KCNQ4 channels, located in the basal membrane of OHCs, regulate K+ efflux. Mutations in KCNQ4 are linked to progressive HL (DFNA2), noise-induced hearing loss, and presbycusis, leading to K+ accumulation, cellular stress, and OHC death. Gene editing or pharmacological activation of KCNQ4 has shown potential in partially preventing HL in mouse models. In this study, we demonstrate KCNQ4 deletion disrupts the localization of key proteins like prestin and BK channels, alters OHC organization, and induces apoptosis in sensory and SC. Spiral ganglion neurons (SGNs) also degenerate over time. Despite these structural changes, noise exposure does not exacerbate OHC damage in our KCNQ4-deficient model. This highlights KCNQ4's role in maintaining ion homeostasis and cochlear function, as its absence triggers widespread dysfunction in the OC. The present study demonstrates that disruptions in a single cell type can have a cascade effect on overall cochlear health. Understanding the molecular and cellular consequences of KCNQ4 mutations is crucial for developing targeted therapies to mitigate progressive HL caused by genetic and environmental factors.